Neuromuscular Disease : Case Studies from Queen Square - Manji, Hadi; Turner, Chris; Evans, Matthew R. B. (Springer London : Imprint: Springer, 2017)
This book provides an accessible guide to neuromuscular disorders using case scenarios from the world-renowned MRC Centre for Neuromuscular Diseases at the National Hospital, Queen Square, London, UK. Fifty genetic and acquired disorders are presented in a practical, easy-to-read format, including those that are common and also some which are rare. Each case covers the history, examination and investigations, including neurophysiology, neuroradiology and neuropathology if appropriate. Discussions of each case include the differential diagnosis, useful clinical pointers and a brief summary of the management of the condition. Neuromuscular Disease: Case Studies from Queen Square is aimed at neurology trainees and consultant general neurologists.- Resumé vydavatel
Keywords: neuromuskulární nemoci; neuromuscular diseases; elektronické knihy; případové studie; electronic books; case studies